1991
DOI: 10.1577/1548-8659(1991)120<0552:rbmoef>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Morphometry of Excavated Floodplain Ponds along the Mississippi River and Their Use as Fish Nurseries

Abstract: We sampled ichthyoplankton, zooplankton, and juvenile fish during May, August, and November 1988 from 15 excavated floodplain ponds along the Mississippi River. In May, densities of larval shad Dorosoma spp. ranged from 1.1 to 87.8/m3 and densities of larval sunfish Lepomis spp. ranged from 0.3 to 19.3/m3 among ponds. Ponds with long (>1,800 m), sinuous shorelines, high volumes (>55,000 m3 ), and variable depth had high ichthyoplankton densities (>50/m3); smaller, low‐volume ponds frequently had low ichthyopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…The importance of the connection of the floodplain lakes with the main river and the occurrence of floods that reach the disconnected lagoons was already evidenced in various studies of fish assemblages (Sabo & Kelso, 1991;Súarez et al, 2004;Amoros & Bornette, 2002;King et al, 2003;Petry et al, 2003Petry et al, , 2004Pompeu & Godinho, 2006;Gubiani et al, 2007). However, specific studies that showed this same pattern for fish larvae assemblages were scarce.…”
Section: Discussionmentioning
confidence: 96%
“…The importance of the connection of the floodplain lakes with the main river and the occurrence of floods that reach the disconnected lagoons was already evidenced in various studies of fish assemblages (Sabo & Kelso, 1991;Súarez et al, 2004;Amoros & Bornette, 2002;King et al, 2003;Petry et al, 2003Petry et al, , 2004Pompeu & Godinho, 2006;Gubiani et al, 2007). However, specific studies that showed this same pattern for fish larvae assemblages were scarce.…”
Section: Discussionmentioning
confidence: 96%
“…Many juvenile riverine fishes were thought to have historically used these floodplains as nurseries (Sabo and Kelso 1991). Models for the reconnection and sustainable use of floodplains have been described (e.g., Opperman et al 2009;Thorp et al 2010) and could be considered in recovery efforts.…”
Section: Sturgeon-specific Considerationsmentioning
confidence: 99%
“…For example, amphibians in ephemeral ponds (Wellborn and others 1996), fish in streams (Schlosser 1991;Fausch and others 2002), cavity nesting birds in dead and dying trees (Martin and Eadie 1999), chickadees (Lima 1985), and large grazing mammals (Walters 2001) all appear to exhibit metapopulation dynamics that could also vary both spatially and temporally. In floodplain rivers, although only the bluegill was examined in this study, a large number of other motile riverine organisms purportedly share this same metapopulation dynamic and are therefore also faced with similar trade-offs (for example, Sabo and Kelso 1991;Meschiatti and others 2000;Slipke and others 2005).…”
Section: Discussionmentioning
confidence: 97%